Barong Bali Performing Arts: A Study Case of Dance Motion Pattern - Limano, Ferric (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research aimed to save the traditional Balinese Barong dance motion patterns and convert them into digital animation. Using the mask was a uniqueness and as one of the characteristics of the traditional dance. Some problems arose in today's global situation: the challenge of eroding local society cultures to be replaced by global cultures. Another factor was the new generation, who loved technology and digitization. The research showed how to make traditional art that had recommendations in new digital media 3D animation. This was necessary to increase interest for the new generation about traditional culture and the creation of digital archives that were easily accessible to learn and develop in this traditional culture. The method was applied qualitatively through approach practice-led research by making experimental data on the dance motion pattern of the head of Barong Bali. Then observations were made and described in animation science, resulting in an academic understanding of motion and 3D digital media production. The results of the research consist of Barong Bali motion pattern in 3D, descriptive explanation of movement patterns, and the process of creating 3D animation digital archives. All of this is expected as recommendations for ways to produce digital archives 3D Animation of another Indonesian traditional culture.